2020
DOI: 10.1021/acs.jnatprod.0c00668
|View full text |Cite
|
Sign up to set email alerts
|

Cannabitwinol, a Dimeric Phytocannabinoid from Hemp, Cannabis sativa L., Is a Selective Thermo-TRP Modulator

Abstract: Cannabitwinol (CBDD, 3), the second member of a new class of dimeric phytocannabinoids in which two units are connected by a methylene bridge, was isolated from a hemp (Cannabis sativa L.) industrial extract. The structural characterization of cannabitwinol, complicated by broadening of 1H NMR signals and lack of expected 2D NMR correlations at room temperature, was fully carried out in methanol-d 4 at −30 °C. All the attempts to prepare CBDD by reaction of CBD with formaldehyde or its iminium analogue (Eschen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…TRPV1 shares the highest sequence identity within the putative CBD binding site as described above at 79%, second only to TRPV2 itself. Additionally, CBD is reported to have the highest efficacy of the vanilloid subfamily at TRPV1 (∼78%) (Chianese et al, 2020).…”
Section: Figure 2 | (A)mentioning
confidence: 99%
See 4 more Smart Citations
“…TRPV1 shares the highest sequence identity within the putative CBD binding site as described above at 79%, second only to TRPV2 itself. Additionally, CBD is reported to have the highest efficacy of the vanilloid subfamily at TRPV1 (∼78%) (Chianese et al, 2020).…”
Section: Figure 2 | (A)mentioning
confidence: 99%
“…Additionally, L537 shows a rotameric change, going from trans in the apo structure to g+ in the CBD-bound structure which is reported to allow accommodation for the aromatic ring of CBD. With two CBDbound cryo-EM structures identifying CBD in the same general location (Pumroy et al, 2019) and a reported efficacy of ∼67% at TRPV2 (Chianese et al, 2020), exploring this region should provide insight on the binding mode of CBD.…”
Section: Trpv2mentioning
confidence: 99%
See 3 more Smart Citations